Threshold Effects in the Relationship Between Inflation and Growth - Senhadji, Abdelhak; Khan, Mohsin (Washington, D.C. : International Monetary Fund, 2000)
This paper reexamines the issue of the existence of threshold effects in the relationship between inflation and growth, using new econometric techniques that provide appropriate procedures for estimation and inference. The threshold level of inflation above which inflation significantly slows growth is estimated at 1-3 percent for industrial countries and 7-11 percent for developing countries. The negative and significant relationship between inflation and growth, for inflation rates above the threshold level, is quite robust with respect to the estimation method, perturbations in the location of the threshold level, the exclusion of high-inflation observations, data frequency, and alternative specifications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet